2019
DOI: 10.1108/bpmj-03-2019-0142
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation in family firms: empirical evidence about internal and external knowledge flows

Abstract: Purpose The purpose of this paper is to shed light on how family firms execute open innovation strategies by managing internal and external knowledge flows (KF) to provide a deeper understanding of family firms’ ability to innovate through traditions and create value across generations. Design/methodology/approach Empirical evidence was collected using an online survey of a sample of 208 Apulian entrepreneurs, who were members of the association of young entrepreneurs of Confindustria in the Apulia region (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 116 publications
(176 reference statements)
0
22
0
Order By: Relevance
“…Within the family business literature, most of the research has explored the outcomes associated with KS. These studies have found that the extent to which family and non-family employees share knowledge within family firms is positively related to the organization's technological capabilities (Zahra et al, 2007), entrepreneurial orientation (Barroso Martı ´nez et al, 2016;Pittino et al, 2018), innovation (Arzubiaga et al, 2019;Calabro `et al, 2019;Casprini et al, 2017;Del Vecchio et al, 2019;Price et al, 2013), internationalization (Fang et al, 2018) and performance (Jaskiewicz et al, 2013).…”
Section: Generation In Controlmentioning
confidence: 99%
“…Within the family business literature, most of the research has explored the outcomes associated with KS. These studies have found that the extent to which family and non-family employees share knowledge within family firms is positively related to the organization's technological capabilities (Zahra et al, 2007), entrepreneurial orientation (Barroso Martı ´nez et al, 2016;Pittino et al, 2018), innovation (Arzubiaga et al, 2019;Calabro `et al, 2019;Casprini et al, 2017;Del Vecchio et al, 2019;Price et al, 2013), internationalization (Fang et al, 2018) and performance (Jaskiewicz et al, 2013).…”
Section: Generation In Controlmentioning
confidence: 99%
“…This argument implies that “embeddedness” (Granovetter, 1985) resulting from network relationships can facilitate trust and thus create the preconditions for successful community knowledge transfer. Open innovation in family firms played a critical role in the innovation process (Del Vecchio et al, 2019). For example, the Association des Champagnes Biologiques (Association of Organic Champagnes), representing organic winegrowers and houses, aims to collect and create a shared knowledge base among its members, promoting the exchange of scientific and technical knowledge to facilitate conversion to organic standards.…”
Section: Applying the Four C's To French Champagne Housesmentioning
confidence: 99%
“…In practice, firms are increasingly striving to extend their innovative capacities through strategic partnerships with lead users who can utilize open innovation effectively, leveraging their value-creating knowledge and innovation capabilities (Franke et al , 2006; Santoro et al , 2018). Such users can function as an external research hub for the firm, providing valuable market information (Del Vecchio et al , 2019; Vrontis and Rossi, 2016).…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%